2016
DOI: 10.1016/j.wem.2015.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Topical Treatments for Chrysaora chinensis Species: A Human Model in Comparison with an In Vitro Model

Abstract: Papain-containing meat tenderizer used as a topical treatment for C chinensis stings may decrease pain. Although there is published experimental support for the concept that in vitro nematocyst discharge correlates with in vivo human pain perception, no definitive randomized controlled trial, including ours, has yet provided incontrovertible evidence of this assertion. Despite this study's limitations, it presents a viable basis for future human studies looking at the efficacy of topical treatments for jellyfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…Additional remedies, such as papain, have been found to be of benefit for the stings of some species ( Table 1 and [ 136 ]), but can hardly be found in loco .…”
Section: Further Considerations and Hints For Future Studiesmentioning
confidence: 99%
“…Additional remedies, such as papain, have been found to be of benefit for the stings of some species ( Table 1 and [ 136 ]), but can hardly be found in loco .…”
Section: Further Considerations and Hints For Future Studiesmentioning
confidence: 99%
“…Urine, a commonly believed folk remedy for jellyfish stings, was even worse than seawater ( Figure 4 ), which aligns with out TSA data showing it elicits ~50% discharge of all cnidae types. These results stress the importance of evaluating first aid protocols using functional activity assays rather than solution-only tests, as they add to a growing number of studies that have shown in vitro examinations are not necessarily predictive of clinically relevant effects [ 22 , 23 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The only study examining potential removal methods was conducted more than 30 years ago, relied solely on in vitro examination of nematocyst discharge in response to potential rinse solutions, and did not include quantitative results, raw data images, or statistical comparisons between treatments [ 21 ]. Recent work has demonstrated that nematocyst discharge in vitro has limited (if any) correlation to sting severity as measured by direct functional assays [ 22 ] or human clinical trials [ 23 ]. Similarly, the only study supporting the use of cold packs for pain relief was uncontrolled and contained no statistical analysis [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…28 Furthermore, both bromelain and papain have been indicated to be useful to neutralize snake venom proteins. 7 Papain, which is reported to be used in traditional medicine for several uses, is known also to break down pro-inflammatory peptides and venom toxins; 19,29 the inactivation of venoms seems to occur mainly when papain is experimentally mixed with venom before treatment. 30 Our data could reveal significant aspects for the use of active principles as protective agents in pharmaceutical products.…”
Section: Discussionmentioning
confidence: 99%